Validation and Factor Structure of the French-Language Version of the Emotional Appetite Questionnaire (EMAQ) - Bourdier, Léna; Lalanne, Christophe; Morvan, Yannick; Kern, Laurence; Romo, Lucia; Berthoz, Sylvie (Frontiers in Psychology, 2017)
The concept of Emotional Eating (EE) is increasingly considered to be implicated in overeating and obesity, and in different subtypes of eating disorders. Among the self-report questionnaires assessing EE, the Emotional Appetite Questionnaire (EMAQ) includes recent advances in this area: it evaluates a broad range of emotions and situations both positive and negative, and the way they modulate food intake (decrease, stability or increase). The main objective of our study was to further investigate the psychometric properties of the French version of the EMAQ in a large sample of students. Participants completed the EMAQ (n=679), the DEBQ (Dutch Eating Behavior Questionnaire) (n=75) and the CIDI-eating disorders screening (Composite International Diagnostic Interview) (n=604). Factorial structure, reliability and validity of the EMAQ were tested. Factorial analyses supported a two-factor (Positive and Negative) structure. The internal consistency indices were satisfactory and results suggest good test-retest reliability for the scale. Convergent and discriminant validity were confirmed from the significant correlations observed between the EMAQ scores and the DEBQ-EE subscale scores. Regarding associations with weight, whereas EMAQ negative scores were positively correlated with BMI, EMAQ positive scores were negatively correlated with BMI. Finally, EMAQ scores differed significantly depending on gender and risk for bulimia nervosa. This study supports the validity and the reliability of the EMAQ, which appears to be a promising instrument to better understand individual differences that could modulate food intake.